Commodity Transport Studies Salt - Planning Commission (Planning Commission, 1967)
Salt, chemically known as sodium chloride, is an inorganic substance which is found in varying concentrations in all animal and vegetable life and is widely distributed over the earth Salt is a necessity of life It gives an agreeable flavour and improves the taste of food It is no less essential for cattle and sheep Cattleicks are an ancient institution in India Salt is also very valuable for agriculture and it has germicidal properties as well It is used as a preserver of food Salt finds many uses in chemical.
Joint Technical Group for Transport Planning Planning Commission